Pengaruh C/N Rasio Berbeda untuk Pembentukan Bioflok pada Media Pemeliharaan terhadap Pertumbuhan dan Kelangsungan Hidup Benih Ikan Betok (Anabas testudineus) - M. Indra Wahyu Pratama; Dade Jubaedah; Mohamad Amin (Research Center for Sub-optimal Lands (PUR-PLSO), Universitas Sriwijaya, 2018)
Pratama et al, 2018. The Effect of Different C/N Ratio in for Biofloc of Formation Culture Media to the Growth and Survival Rate of Juvenile Climbing Perch (Anabas testudineus). JLSO 7(1):66-73.Â Climbing perch fish resources still have a problem due to this fish is still obtained only through capture and also the growth of climbing perch fish is slow. The solutions to increase the growth of the climbing perch fish is by applying biofloc technology for climbing perch fish culture. The purpose of this research was to know the effect of different C/N ratio on the growth of climbing perch fish (Anabas testudineus) juvenille with biofloc farming system. This research used a completely randomized design consist of four treatments and three replications. The treatments were without molase (P0), molase with C/N ratio 15 (P1), C/N 20 (P2) and C/N ratio 25 (P3). The results showed that C / N ratio 20 was the best treatment with absolute length of growth of 1.33 cm, absolute growth of weight 1.92 g, survival rate of 99.17% and feed efficiency 138.06%.